2014
DOI: 10.1084/jem.20140131
|View full text |Cite
|
Sign up to set email alerts
|

Niche displacement of human leukemic stem cells uniquely allows their competitive replacement with healthy HSPCs

Abstract: Spatial localization of primitive leukemic cells is restricted to niches shared with their normal counterparts, and their ability to retain occupancy of these niches is rivaled by normal HSPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…Immature CD34 + leukemic cells were located in the endosteal regions of bone indicating that they shared hematopoietic niches C.F. Krombholz et al 604 haematologica | 2016; 101(5) 41 The lineage composition of engrafted JMML cell progeny clearly differed from that of xenotransplanted cord blood-derived healthy CD34 + cells, where B cells predominated and only minor myeloid populations were observed. Importantly, xenotransplanted mice showed a chronic disease course with a median survival of more than 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Immature CD34 + leukemic cells were located in the endosteal regions of bone indicating that they shared hematopoietic niches C.F. Krombholz et al 604 haematologica | 2016; 101(5) 41 The lineage composition of engrafted JMML cell progeny clearly differed from that of xenotransplanted cord blood-derived healthy CD34 + cells, where B cells predominated and only minor myeloid populations were observed. Importantly, xenotransplanted mice showed a chronic disease course with a median survival of more than 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicated that leukemic cells hijack the homeostatic mechanisms of normal HSCs and take refuge in the BM niche [19,20] (Fig. 1).…”
Section: Deregulated Communication Between Cancer Cells and The Organmentioning
confidence: 99%
“…Treatments targeting self-reinforcing leukemic niches especially when combined with conventional chemotherapy or molecular drugs might represent additional therapeutic options that might fulfill this clinical requirement. Various studies have demonstrated that LSCs and HSCs might share the same bone marrow niches [25,26,32] and compete for vacant niches as the number of these areas within the BM is limited [29]. Since these malignant niches provide a shelter for LSCs [79,82,83] and also specify their self-renewal properties [10,22,23] an attractive therapeutic strategy could be to dislodge these cells from their niche by targeting the CXCR4/CXCL12 interaction.…”
Section: Potential Targetsmentioning
confidence: 99%
“…Recently, a phase I/II clinical trial based on this combination has provided beneficial results [106] and additional trials with Plerixafor with or without G-CSF in combination with conventional chemotherapy are currently ongoing as front-or second-line therapy in AML. Even more recently, an exciting observation was made: CXCR4 targeting combined with healthy cord blood HSPC (CBHPSCs) infusions appears to significantly improve allogeneic HSCT results, due to the fact that these cells might potentially function as effector cells [32]. In co-transplantation experiments, CB-HPSCs were able to out-compete leukemia initiating cells (L-ICs) for BM niche occupancy in a cell dose-dependent manner and ultimately disrupted L-IC long-term renewal.…”
Section: Potential Targetsmentioning
confidence: 99%
See 1 more Smart Citation